Investigating Verticillium wilt occurrence in cotton and its risk management by the direct return of cotton plants infected with Verticillium dahliae to the field - Zhang, Guangjie; Meng, Zhuo; Ge, Hao; Yuan, Jiali; Qiang, Song; Jiang, Ping’an; Ma, Deying (Frontiers in Plant Science, 2023)
Verticillium wilt is one of the most crucial diseases caused by Verticillium dahliae that threatens the cotton industry. Statistical results showed that the return of cotton plants infected with V. dahliae to the field might be an essential cause of the continuous aggravation of cotton Verticillium wilt. The correlation among the cotton plants infected with V. dahliae returning to the field, the occurrence of Verticillium wilt, and the number of microsclerotia in rhizosphere soil need further investigation. A potted experiment was carried out to explore the effects of the direct return of cotton plants infected with Verticillium dahliae to the field on the subsequent growth and Verticillium wilt occurrence in cotton. As a risk response plan, we investigated the feasibility of returning dung-sand (i.e., insect excreta) to the field, the dung-sand was from the larvae of Protaetia brevitarsis (Coleoptera: Cetoniidea) that were fed with the V. dahliae–infected cotton plants. The results demonstrated that the return of the entire cotton plants to the field presented a promotional effect on the growth and development of cotton, whereas the return of a single root stubble or cotton stalks had an inhibitive effect. The return of cotton stalks and root stubble infected with V. dahliae increased the risk and degree of Verticillium wilt occurrence. The disease index of Verticillium wilt occurrence in cotton was positively correlated with the number of microsclerotia in the rhizosphere soil. The disease index increased by 20.00%, and the number of soil microsclerotia increased by 8.37 fold in the treatment of returning root stubble infected with V. dahliae to the field. No Verticillium wilt microsclerotia were detected in the feed prepared from cotton stalks and root stubble fermented for more than 5 days or in the transformed dung-sand. There was no risk of inoculation with Verticillium wilt microsclerotia when the dung-sand was returned to the field. The indirect return of cotton plants infected with V. dahliae to the field by microorganism–insect systems is worthy of further exploration plan of the green prevention and control for Verticillium wilt and the sustainable development of the cotton industry.